DOI: 10.17918/etd-7823
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the benefits of after-school arts program in Wuhan city-China

Abstract: The penetration of atomic hydrogen through defect-free graphene was generally predicted to have a barrier of at least several eV, which is much higher than the 1 eV barrier measured for hydrogen-gas permeation through pristine graphene membranes. Herein, our density functional theory calculations show that ripples, which are ubiquitous in atomically thin crystals and mostly overlooked in the previous simulations, can significantly reduce the barriers for all steps constituting the mechanism of hydrogen-gas per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
4
1
Order By: Relevance
“…used POI to identify the URF of the Guangzhou-Foshan The urban-rural fringe area of Wuhan is 1482.35 km 2 in total, and it accounts for 17.30% of the city's total area. This result is slightly smaller than the 1746 km 2 area of the URF of Wuhan in 2016 identified by Xiong, N. using NPP-VIIRS as the data source, which may be related to the saturation and spillover effect of NPP-VIIRS [40]. However, the area ratio of URF determined in this study is very similar to that determined by Zhang, J. using NTL and POI fusion data.…”
Section: Spatial Analysis Of Urban and Rural Fringe In Wuhancontrasting
confidence: 50%
“…used POI to identify the URF of the Guangzhou-Foshan The urban-rural fringe area of Wuhan is 1482.35 km 2 in total, and it accounts for 17.30% of the city's total area. This result is slightly smaller than the 1746 km 2 area of the URF of Wuhan in 2016 identified by Xiong, N. using NPP-VIIRS as the data source, which may be related to the saturation and spillover effect of NPP-VIIRS [40]. However, the area ratio of URF determined in this study is very similar to that determined by Zhang, J. using NTL and POI fusion data.…”
Section: Spatial Analysis Of Urban and Rural Fringe In Wuhancontrasting
confidence: 50%
“…This experiment found that the mobile map navigation icons with regular color distribution have better usability than monochrome navigation icons and navigation icons with a random color distribution. Xiong (2019) pointed out that visual interface design is an important factor affecting user usability. As we all know, layout is an important element of interface design.…”
Section: Discussionmentioning
confidence: 99%
“…The corroding and covering state at sample surface was observed and recorded. Calculated two samples of each group, then took the mean [6,7].…”
Section: Experiments Methodsmentioning
confidence: 99%